Desenvolvimento e otimização do extrato padronizado de Spondias mombin (cajazeira): atividades anti-inflamatória e anti-herpes do extrato e da geraniina - Silva, Thiala Soares Josino da (2016)
Spondias mombin L. (Anacardiaceae) is a large-sized tree, fruit, common in western India, Mexico, Peru, Brazil and popularly known as cajazeira. All parts have been used by traditional medicine. The plant is part of REPLAME (List of Medicinal Plants) the state of Ceará and project Vivas pharmacies with the indication for the treatment of herpes. The aim of this study was to develop a standardized fitoproduto from the leaves of S. mombin, and evaluate its potential anti-inflammatory and antiviral (Herpes simplex 1). For that were initially established the method of preparation (drying oven with circulation / air renewal) at 60 ± 5 ° C for 4 hours and the specifications for quality control of plant drug (DV). The extraction method for obtaining a standardized extract of S. mombin was dynamic maceration for 2.5 h at 30 ° C and relative DV: solvent (30% ethanol in water) 0.3, wherein the total phenol content ( FT: 17.52 mg / mL), dry (RS: 7.12%, w / v) and chromatographic profile by HPLC-DAD (chlorogenic acid - AC: 0.83 mg / ml and Geraniina - GR: 7, 37 mg / ml). In the evaluation of potential anti-inflammatory, S. mombin extract (ESM) (1, 10, 50, 100 ug / ml) partially inhibited the release of MPO (Myeloperoxidase) induced by PMA (Folbol-12-myristate-13-acetate ), with best effect seen at the highest concentration (% inhibition: 50.4), while the standard GR (1, 10, 25, 50 and 100 ug / ml) induced a dual effect, increasing neutrophil degranulation induced by PMA in smaller concentrations (1 - 25 mg / mL) and this inhibits (40.3 and 83.5%) in higher concentrations (50 and 100 ug / ml). As the concentration of 200 / ml ESM showed cytotoxicity in human neutrophils in the MTT test. In the assessment of cytotoxicity on Vero cells, the ESM showed CC50 = 1680 mg / mL and CC50 GR = 392.5 mg / mL, whereas the standard PFA (phosphonoformic acid) showed CC50 = 392.5 mg / mL. In the evaluation of the antiviral potential, the ESM was more potent with IC 50 = 342.5 ug / ml compared to GR (IC 50 = 417.5 ug / ml) and PFA (IC50 = 570 ug / ml), and had an index selectivity (IS) next to the PFA. The IS GR was 0.94. The results obtained in this study allowed to establish, in an unprecedented manner, methods and specifications for the production and quality control of both the DV as the ESM. Furthermore, both ESM as geraniina (bioactive marker) possess anti-inflammatory activity and anti-herpes (herpes simplex 1)